A bifunctional optical probe based on ESIPT-triggered disalicylaldehyde with ratiometric detection of iron and copper ions. (1st January 2021) - Shen, Yin-Jing; Zhang, Kun
Graphical abstract: An ESIPT-contained disalicylaldehyde H2 Qj1 shows rapidly (60 s) and sensitively turn-off fluormetric and colorimetric responses for Fe(III) (LOD/0.40 μΜ) and Cu(II) (LOD/0.21 μΜ) which also have ratiometric features (1:1 and 2:1 coordination modes). Our proposed smartphone-based analysis provides a convenient technique to determine two cations in water samples. Highlights: An ESIPT-triggered disalicylaldehyde efficiently responses to Fe(III) and Cu(II). Smartphone-based analysis provides a convenient detection technique for two ions. This probe shows outstanding determination results for two ions in tap water. Abstract: In this paper, we design and synthesize an N -linked disalicylaldehyde H2 Qj1 based on the economical substrates, and it is composed of two identical salicylaldehyde moieties with the intramolecular ESIPT character. During the process of sensing heavy metal ions, it is found that the ESIPT state of H2 Qj1 can be rapidly (60 s) destroyed by Fe(III) and Cu(II), resulting in the turn-off fluormetric and colorimetric responses. Serial fluorescence and absorption titration experiments reveal that the H2 Qj1 -Fe(III) and H2 Qj1 -Cu(II) sensing systems are ratiometric and their corresponding coordination modes are 1:1 and 2:1. Especially, their LOD values are as low as 0.40 μΜ and 0.21 μΜ which are comparable to reported examples. Moreover, we also develop a convenient technique to detect Fe(III) and Cu(II) using paper-based sensing devices together with smartphone-based RGB analysis method which will rapidly provide the precise determination results, even in the tap water sample. Therefore, this bifunctional disalicylaldehyde H2 Qj1 is taken as a useable platform to monitor Fe(III) and Cu(II) and offers some valuable lights for further optical probes.